Access to Drugs and Out of Pocket Expenditure in Primary Health Facilities - Thapa, Arjun Kumar; Ghimire, Namita; Adhikari, Shiva Raj (Journal of Nepal Health Research Council, 2017)
Background: The Government of Nepal promulgated health as a human right via Interim constitution and implemented Free Health Service Program in 2008 as a commitment to universalize basic health care services. So, the aim of this study was to understand reported access to medicine and health care services received by outpatients in public primary facilities. Methods: The study followed cross sectional study design. Two hundred and thirty-four For data 234 out patients were interviewed on the day of the field visit in March and October 2014 across 28 primary health facilities of seven purposively selected districts representing three ecological belts and five development regions of the country. Results: Our study revealed that the average number of medicines prescribed per patient was 2.65 per case in primary public health facilities, of which 91.2% were dispensed. Around 86.6% dispensed medicines were appropriately labeled and 84% of outpatients had proper knowledge of dosage and timing of medicine use. Around 55.6% of outpatients purchased some or all prescribed medicines from nearby private facilities which were not available in public facilities. Around 40% of them travelled more than half an hour to reach the facility. Conclusions: The gap in medicines prescribed and dispensed, Out of Pocket expenditure coupled with opportunity cost of travelling, appear as hurdles in access to basic health care services. So increasing free medicines list in public primary facilities with all round the year availability might answer major part of the problem. Keywords: Free health care; out of pocket payment; primary facilities.